Source Studies of the History of Defense Structures of Samarkand During the Middle Ages (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2023)
This is Samarkand city planning in the article indispensable part calculated defense walls and facilities about information gave written sources study done. Also archaeological excavations as a result determined of cities defense to the walls about archaeological findings written in sources given data with compared.